Teaching science creatively - Davies, Daniel John 1962- (London Routledge, 2011)
"Offers ideas to involve your students and demonstrate the potential of creative teaching to develop children's knowledge, skills, understanding and attitudes. Underpinned by theory and research, it offers informed and practical support to both students in initial teacher education, and practising teachers who want to develop their teaching. Illustrated by examples of children's work, this book explores the core elements of creative practice in relation to developing enthusiastic, passionate science learners."
Introduction -- 1. Can science be creative? -- 2. Teaching creatively and teaching for creativity -- 3. Teaching science creatively in the early years -- 4. Cross-curricular starting points -- 5. Creative exploration : the New Zealand model Ian Milne -- 6. Collaborative science enquiry -- 7. Using language creatively in science -- 8. Using new technologies creatively in science -- 9. Using the outdoors creatively in science -- 10. The wider role of the creative primary science teacher -- Conclusion.
Keywords: Science -- Study and teaching (Primary) -- Activity programs; Science -- Study and teaching (Elementary) -- Great Britain; Science -- Study and teaching (Elementary) -- Great Britain -- Activity programs; Creative teaching -- Great Britain